6G Architecture Design: Evolution or Disruption? - Oliveira, Daniel Ricardo Cunha; Moreira, Rodrigo; Rosa, Pedro Frosi; Silva, Flávio de Oliveira (Anais do Workshop de Redes 6G (W6G), 2022)
In this paper, we aim the shed light on an intriguing question in a essential concept concerning the future 6G network architecture: can it be based on an evolution of the 5G network, or should it follow a disruptive path? Based on the analysis of 6G expected applications, requirements, and enablers, we found that there will not be an exclusively evolutionary or disruptive approach to this architecture, but network solutions that should complement each other to cover all the needs required by the 6G service.